The Impact of Western Sanctions on Trade of Russia with Countries from the Eurasian Economic Union - Graf, Dmitri; Bolotov, Ilya; De Castro, Tereza; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
countries from the Eurasian Economic Union (EAEU) since 2014 and with a particular focus on sanctions imposed in 2022. Hereby, the aim of the thesis is to assess whether the sanctions have resulted in an increase of intra-union trade with respect to Russia as a tool to mitigate the impact of Western sanctions on Russia’s trade. Furthermore, the sectors machinery, energy, and agriculture will receive a particular focus. For the investigation of the hypotheses, a mixed-methods approach will be applied that includes academic sources, non-academic sources, and empirical data from trade data sets, covering the period 2013-2023. The thesis is structured in the following way: Firstly, it establishes a theoretical framework about the EAEU, sanction theory, and Russia’s trade with the EAEU. Secondly, the thesis focuses on the impact of Western sanctions on Russia’s trade dynamics with the EAEU, which includes also sectoral perspectives to assess changes. At the end, the third chapter goes more into detail and investigates the evolvement of the bilateral trade relationship between Russia and Kazakhstan under Western sanctions against Russia, which also illustrates adaptation strategies of Kazakhstan towards Russia. Findings include, among other, that trade between Russia and the EAEU has increased since the beginning of the EAEU, especially in sectors such as machinery and electronics after the imposition of far-reaching sanctions in 2022.
Vedoucí práce: Ilya Bolotov
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses